Psychological type profile of ministers of word and sacrament within the United Reformed Church (URC). Issue 9 (21st October 2022) - Lewis, Christopher Alan; Burgess, John Hopkins; Francis, Leslie J.
ABSTRACT: Preference within the perceiving process (sensing or intuition) is one of the main features within psychological type theory that differentiates clergy serving within different streams of the Christian Church. Previous research has identified a higher proportion of intuitive types among Church of England clergy than among clergy serving within the Free Churches (Baptist, Methodist, Salvation Army). New data from 93 ministers serving within the United Reformed Church suggest that this denomination may occupy a position between the Church of England and other Free Churches, with 55% of male ministers, and 53% of female ministers preferring intuition.